Welfare gains of bailouts in a sovereign default model - Roberto Pancrazi; Hernán D. Seoane; Marija Vukotic (Bank of Finland, 2019)
We examine the welfare effects of bailouts in economies exposed to sovereign default risk. When a government of a small open economy requests a bailout from an international financial institution, it receives a non-defaultable loan of size G that comes with imposed debt limits. The government endogenously asks for the bailout during recessions and repays it when the economy recovers. Hence, the bailout acts as an imperfect state contingent asset that makes the economy better off. The bailout duration is endogenous and increases with its size. The bailout size creates non-trivial tradeoffs between receiving a larger amount of relatively cheap resources precisely in times of need on the one hand, and facing longer-lasting financial constraints and accumulated interest payments, on the other hand. We characterize and quantify these tradeoffs and document that welfare gains of bailouts are hump-shaped in the size of bailout loans.
URN:NBN:fi:bof-201912181715
Keywords: E44; F32; F34; 330